Aspectos histologicos de testículos da tuvira (Gymnotus spp.) submetida à reprodução por diferentes indutores hormonais - Rosa, Roberta Martins (2015)
The objective of this study was to analyze the histological aspects of tuvira testes (Gymnotus spp.) subjected to reproduction by different hormonal inducers. Sixty tuviras were captured, approximately 40g ± 10g and transported to fish sector of PUC -Goiás. The fish were placed during the period from December 2013 to February 2014, in a period of adaptation to 90 days. Using a randomized design, has defined four treatments with ten repetitions or ten animals per box, each animal being a repeat. For induction of tuvira, three hormones were tested. The control group, used saline at 2%, the others group used: the extract of carp pituitary (EBHC), equine chorionic gonadotropin (ECG) and synthetic analogue of gonadotropin-releasing hormone (GnRH-a). The three hormones were applied in two doses, the first one (preparatory) in order to promote full maturation of gametes and the second for the purpose of releasing the gametes. For histological analysis, were killed five males per treatment, the testicles were removed and evaluated by the ventral section of the coelomic cavity and quickly stored in Bouin s fixative solution for twenty-four hours. After fixation of the testicles, slides were prepared and photographed at the Molecular Systematics Laboratory of the Federal University of Viçosa. Were photographed 15 frames per fish in light microscope, where these ten images were analyzed using the software Image- Pro Plus ®. The volume ratio occupied by the components of testicular parenchyma (seminiferous tubules and intertubular tissue) was determined by counting 2660 points projected on ten images obtained at random, with 266 points in each image. Populations were quantified spermatogonia type A, type B, primary spermatocytes, secondary spermatocytes, spermatids and Sertoli cells (S) and the proportion of the lumen. Data were analyzed by comparison of means by Tukey test, performed by the Statistical Analysis System software - SAS. The results indicate that the GnRHhormone showed a greater ability to promote final maturation in the testes, followed by ECG hormone. The EBHC hormone failed to promote the final maturation induced tuviras, suggesting a longer duration than other hormones used. One possible explanation for the greater induction of the GnRH-hormone would be the ability to produce endogenous gonadotropins. Other hormones have justified their answers in the specificity of membrane receptors on Sertoli cells and Leydig. Researching the tuviras response to hormonal inductors, are required.